The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1037/0022-3514.84.6.1140
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of value from fit.

Abstract: People experience regulatory fit when they pursue a goal in a manner that sustains their regulatory orientation (E. T. Higgins, 2000). Five studies tested whether the value experienced from regulatory fit can transfer to a subsequent evaluation of an object. In Studies 1 and 2, participants gave the same coffee mug a higher price if they had chosen it with a strategy that fit their orientation (eager strategy/promotion; vigilant strategy/prevention) than a strategy that did not fit. Studies 3-5 investigated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
606
6
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 565 publications
(669 citation statements)
references
References 55 publications
35
606
6
14
Order By: Relevance
“…As further evidence of risk aversion, people with a stronger prevention focus disengage more readily when an ongoing task becomes relatively difficult. Poor fit between a person's goal orientation and goal pursuit strategies leads to poorer behavioral performance, devaluation of potential incentives, and a greater likelihood of disengagement (e.g., Higgins, 2005;Higgins, Idson, Freitas, Spiegel, & Molden, 2003).…”
Section: Approach-avoidance Frameworkmentioning
confidence: 99%
“…As further evidence of risk aversion, people with a stronger prevention focus disengage more readily when an ongoing task becomes relatively difficult. Poor fit between a person's goal orientation and goal pursuit strategies leads to poorer behavioral performance, devaluation of potential incentives, and a greater likelihood of disengagement (e.g., Higgins, 2005;Higgins, Idson, Freitas, Spiegel, & Molden, 2003).…”
Section: Approach-avoidance Frameworkmentioning
confidence: 99%
“…Moskowitz and Côte (1995) found that individuals who scored high on trait measures of agreeableness, quarrelsomeness, or dominance experienced greater positive affect when they were able to behave in their preferred agreeable, quarrelsome, or dominant manner. Similarly, research on regulatory fit finds that when individuals engage in a task using their preferred strategic manner, they enjoy what they are doing more, are more strongly engaged, and assign greater value to the outcomes they experience (Cesario, Grant, & Higgins, 2004;Freitas & Higgins, 2002;Higgins, Idson, Freitas, Spiegel, & Molden, 2003). When couples have complementary strategic preferences and are able to divide joint tasks in ways that allow each of them to behave in their preferred manner, the increased positive affect, engagement, and value they experience may lead to increased satisfaction with the relationship as a whole.…”
Section: Joint Goal Pursuit and Relationship Well-beingmentioning
confidence: 99%
“…Higgins postulates that this value derived from fit manifests in five ways: (a) increased preference for or inclination toward the behavior (Higgins, Roney, Crowe, & Hymes, 1994), (b) increased motivation to engage in behavior (Cesario, Grant, & Higgins, 2004;Shah, Higgins, & Friedman, 1998), (c) imagining feeling good about engaging in the behavior (i.e., positive prospective feelings; Higgins, 2000), (d) feeling good after engaging in the behavior (i.e., positive retrospective feelings; Freitas & Higgins, 2002), and (e) assigning a greater value to the behavior (e.g., perceiving the behaviors as more enjoyable, more worthwhile, or worth more money; Higgins, Idson, Freitas, Spiegel, & Molden, 2003). Evidence from laboratory-based studies, as noted, indicates that regulatory fit positively affects each of these value-related domains.…”
mentioning
confidence: 99%